Low threshold, amplified spontaneous emission from core-seeded semiconductor nanotetrapods incorporated into a sol-gel matrix - Liao, Yile (2013)
Wet-chemically synthesized CdSe seeded CdS nanotetrapods incorporated into silica matrices have been explored as high performance nanocrystal-based optical amplifiers. Varying the physical dimensions of the tetrapods allowed for room temperature biexcitonic amplified spontaneous emission (ASE) at wavelengths corresponding to either the CdSe core or CdS arms, while higher pump intensities resulted in ASE from a higher CdSe excited state. These results collectively indicate that such heterostructured tetrapods can facilitate tunable, multiple-wavelength lasing across a wide spectral range from a single nanostructure.